COMPONENTIAL ANALYSIS OF THE MEANING FIELD OF HAIR STYLING ACTIVITIES IN INDONESIAN - Ramadhan, Achmad Hadid Rafly Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This research is a descriptive linguistic research that aims to describe lexemes that refer to hair styling activities in Indonesian. The data in this study were inventoried using an introspective method and analyzed using a componential analysis approach, namely by (1) grouping lexemes into several subfields based on hair styling methods and techniques, namely hair styling activities based on shaping, tying, and coloring, (2) describing the meaning components of each lexeme, (3) identifying the same meaning components in each lexeme, (4) compiling a differentiation matrix for each lexeme, (5) determining the status of semantic features in the matrix using the symbols −, 0, and +, and (6) concluding the meaning relationships between lexemes through diagrams based on the results of the meaning component analysis. The results of the study show that there are 16 lexemes that form the meaning field of hair styling activities in Indonesian, namely menyisir, menyasak, mengeriting, meluruskan, memoni, menyibak, mengibas, menggulung, mengikat, mengonde, mengepang, menguncir, menyemir, mewarnai, mem-bleaching, dan highlight.. This analysis produces lexical definitions that show the relationships and differences in meaning between lexemes based on their semantic components.